Grinting Fried Onion: Empowerment of Grinting Youth Enterpreneur based Digital Village - Halim Purnomo Halim; Tumin Tumin; Firman Mansir; Dien Noviany Rahmatika Novi (Universitas Pancasakti Tegal, 2021)
The purpose of devotion is to provide knowledge and skills of online marketing to the younger generation by utilizing e-commerce technology to develop youth Small and Medium Enterprises (SMEs) in Grinting Village. The participants consisted of 25 member SMEs of fried onions specifically for the people of Grinting Village. The materials provided include the creation of an online shop account, product uploads, marketing up to the online financial system. This service was carried out in Grinting Village, Bulakamba District, Brebes Regency, Central Java with the target of the community and the younger generation, especially the entire management of Karang Taruna Garuda Jaya Grinting Village. This cooperation is based on the cooperation between Universitas Muhammadiyah Yogyakarta and grinting village government. The method used is to provide training materials through presentations accompanied by e-commerce implementation training. The achievement of this devotion is the implementation of the service activities in accordance with the expected number of participants as many as 25 administrators and members of Karangtaruna Garuda Jaya Grinting Village independently can develop SMEs for economic independence. Participants gain knowledge and skills about e-commerce implementation to capture developing and mentoring SMEs in local villages. Keywords: SMEs, Grinting, empowerment, e-commerce, training